Pustaha laklak no. 252, Museum Simalungun & Pustaha laklak Mandailing (Proyek Pengembangan Media Kebudayaan, Departemen P & K, 1979)
Translation of early bark manuscripts relating to the customs and practices of the Simalungun and Mandailing, Batak subgroups, in Sumatera Utara.